Inter simple sequence repeat (ISSR) primers for effective genetic polymorphism determination in Lasiodiplodia theobromae infecting Jatropha curcas in Malaysia. - Tan, Yee How; Vadamalai, Ganesan; Wong, Mui Yun; Naderali, Neda (2012)
Botryosphaeria rhodina (anamorph Lasiodiplodia theobromae) in the phylum Ascomycota is a common pathogen on more than 500 tree species in the tropics and subtropics that cause stem canker and dieback disease resulting in a high mortality rate and up to 50% yield loss in Jatropha curcas holdings in Malaysia. Jatropha is known to be important for biofuel production. An inter simples equencere peat( ISSR) technique, PCR based method that involves amplification of DNA segment between two identical microsatellite repeat regions, was employed to analyze genetic diversity among 20 isolates of stem canker pathogen infecting Jatropha plantations in Peninsular Malaysia.Seven ISSR primers were used for initial screening of the twenty isolates of which only four primers (ISSR4, ISSR6, ISSR8 and UBC835) created reproducible and interpretable amplification products. The four primers produced a total of 483 amplified bands of which 126 bands were polymorphic.The percentage of polymorphic DNA fragments ranged from 22.6% to 29.9%. The primer sequence which was most commonly amplified was (AG)n. Jaccard's genetic similarity index was employed to construct a dendrogram and nine clusters were obtained. Based on the clusters observed, there was no correlation between genotype and location. ISSR markers provided a quick, reliable and informative way for establishing the genetic diversity of the pathogen.